Color regulation for dual-states of electrochromic polymer accompanied with light induced coloration effect - Zhuang, Shiwei (2022)
With the developing demand for the smart stimuli-responsive materials, the functional conjugated polymers are appealing for the electrochromic materials, due to their adjustable structure, rapid switching time and facile processability. Series of innovative conjugated electrochromic polymers consisting of triphenylamine or phenothiazine group have been designed and synthesized. Other than the conventional electrochromic polymers, our designed polymers can control colors of both reduction and oxidation states with applied external potential. With incorporation of side anode electrochromic group, the polymers bearing triphenylamine group can achieve grey-blue color at oxidation states and those containing phenothiazine group can present dark purple color at their oxidation states. With further modification of polymer backbone, the reduction colors of electrochromic polymers can be regulated as well. Therefore, the effective combination of anode and cathode electrochromic materials in one can realize color regulation for the dual-states as expected. Additionally, the polymers bearing triphenylamine group can further achieve light induced coloration effect as the triphenylamine group can act as light-induced energy source to drive the reduction of polymer backbone. Therefore, the design and effects of these polymers can broaden application range of electrochromic polymers and provide new strategies for energy saving material design.